Customizable TDI-based whole body X-ray scanner - Durmaz, Fevzi Aytaç. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2020., 2020)
Medical X-ray systems are the gold standard in certain cases of medical diagnostics for over 100 years. The main scope of our studies is to develop a new full-body X-ray scanner device using line scanner detectors, and a plug and integrate hardware controlled system, this new device called SyncBox. Main focus of this particular dissertation is to control the total electronics and mechatronic systems of the device. full body X-ray scanner will be useful for trauma studies and bone surveys, where its high image resolution will help to identify more detailed images. SyncBox control system is a novel patented idea, that helps to integrate X-ray device components more easily and securely. Syncbox will help researchers to build up new, customizable devices faster, and it could begin a new developmental and even an industrial standard for X-ray imaging.|Keywords : Medical Imaging, Open Source Hardware, Medical Device Development, X-ray Applications, X-ray Imaging Hardware.
Keywords: Diagnostic imaging.; X-ray lasers.; Medical instruments and apparatus.; Magnetic resonance imaging.